Youth Violence (Bullying) in Schools and the School's Efforts to Overcome It: Case Study at SMPN 1 Leuwiliang - Nuraini; Ni’am Rohmatullah; Elsa Kusuma (al-Afkar, Journal For Islamic Studies, 2024)
Violence and bullying among teenagers in the school environment is a phenomenon that has serious impacts on the psychosocial well-being and academic achievement of students. The purpose of this study is to identify incidents of adolescent violence at school and analyze the efforts made by the school to address them. The research method used is a qualitative approach by conducting a case study at SMPN 1 Leuwiliang. The findings show that adolescent violence at school includes various forms such as verbal, physical, and cyber. The causes of this incident include social, psychological, and environmental aspects. The school has implemented various strategies to combat adolescent violence, including training programs for teachers and students, anti-bullying campaigns, and the application of sanctions against perpetrators. However, the challenges faced by the school are due to the lack of awareness and active participation from various parties, including parents and the surrounding community. Therefore, creating a safe and supportive environment for students requires interdisciplinary collaboration between schools, families, and communities. This research contributes to a better understanding of adolescent violence in schools and provides recommendations for developing more effective policies and practices to combat this phenomenon.